Specials - Westerfeld, Scott (Westerfeld, Scott. Uglies, 2011)
Tally has been turned into a Special, a superamped fighting machine engineered to keep the Uglies down and the Pretties stupid. She is offered a chance to stamp out all the rebels of New Smoke permanently. She must choose between the mission that she's programmed to complete and the faint memory of her feelings when she was an Ugly turned Pretty.